Complications and Short-Term Patient Outcomes of Periacetabular Osteotomy for Symptomatic Mild Hip Dysplasia. Issue 1 (January 2017) - Ricciardi, Benjamin F.; Fields, Kara G.; Wentzel, Catherine; Nawabi, Danyal H.; Kelly, Bryan T.; Sink, Ernest L.
Introduction: The purpose of our study is to identify complications and early functional outcome scores in patients treated with periacetabular osteotomy (PAO) for mild acetabular dysplasia. Methods: The study population consisted of patients from a single centre prospective hip registry undergoing PAO with mild acetabular dysplasia (LCEA ≥18° and ≤25°; n = 27 patients; Mild Dysplasia group). A comparison group of patients undergoing PAO with more severe acetabular dysplasia (lateral centre-edge angle [LCEA] ≤17°; n = 50 patients; Severe Dysplasia group) were included as a comparison cohort. Demographics, radiographic findings, complications, and functional outcome scores were recorded at 6 months, 1 year, and 2 years postoperatively (mean 15 months [range 6-30]). Results: Demographic characteristics were similar in patients with mild dysplasia undergoing PAO compared with more severe dysplasia. Achievement of radiological correction and complication rates were not different between the 2 groups. Functional outcome scores showed similar improvements in modified Harris Hip Score (mHHS), hip outcome score (HOS) activities of daily living (ADL), HOS Sport, and the international Hip Outcome Tool-33 (iHOT-33) at all time points between the 2 groups with over 90% of patients in the mild dysplasia group achieving a minimum important change (MIC) in functional outcome scores at final follow-up. Discussion: Patients with symptomatic mild acetabular dysplasia undergoing PAO have similar complication rates and functional outcomes as a cohort of patients with more severe dysplasia.